Utility privatization and the needs of the poor in Latin America : have we learned enough to get it right? - Estache, Antonio 1957- (Policy research working paper, 2000)
Do Latin America's poor households lose from the privatization of infrastructure? How can policymakers minimize the risk of losses while promoting competition and private financing of infrastructure?